Optimal Design of a Bio-Inspired Anthropocentric Shoulder Rehabilitator - S. K. Mustafa; G. Yang; S. H. Yeo; W. Lin (Applied Bionics and Biomechanics)
This paper presents the design of a bio-inspired anthropocentric 7-DOF wearable robotic arm for the purpose of stroke rehabilitation. The proposed arm rehabilitator synergistically utilizes the human arm structure with non-invasive kinematically under-deterministic cable-driven mechanisms to form a completely deterministic structure. It offers the advantages of being lightweight and having high dexterity. Adopting an anthropocentric design concept also allows it to conform to the human anatomical structure. The focus of this paper is on the analysis and design of the 3-DOF-shoulder module, called the shoulder rehabilitator. The design methodology is divided into three main steps: (1) performance evaluation of the cable-driven shoulder rehabilitator, (2) performance requirements of the shoulder joint based on its physiological characteristics and (3) design optimization of the shoulder rehabilitator based on shoulder joint physiological limitations. The aim is to determine a suitable configuration for the development of a shoulder rehabilitator prototype.